2010
DOI: 10.1177/154193121005401961
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Measure of Situation Awareness: The Case for Eye Movement Analysis

Abstract: Situation awareness (SA) is a measure of an individual's knowledge and understanding of the current and expected future states of a situation. While there are numerous options for SA measurement, none are currently suitable in dynamic, uncontrolled environments. The current research explored the relationship between direct measures of SA and eye tracking measures as a first step in the development of an unobtrusive measure to be used in environments not suited for existing SA measurement methods. Results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 17 publications
7
50
1
Order By: Relevance
“…Under the same experimental difficulty, the dispersed group exhibited a higher SA than the clustered group. This result is consistent with the findings of Moore and Gugerty [31] that participants whose attention distribution is more extensive could consider the information of each functional area in the simulated tower control interface and have a better SA. Regardless of the group, the participants' SA decreased as the experimental difficulty increased because increasing the experimental difficulty greatly increased the demand for attention resource (Demand), while the situational understanding Review 13 (1) (2020) 133 -140 (Understand) and the supply of attention resource (Supply) remained limited.…”
Section: Sa Of Tower Controllerssupporting
confidence: 92%
See 3 more Smart Citations
“…Under the same experimental difficulty, the dispersed group exhibited a higher SA than the clustered group. This result is consistent with the findings of Moore and Gugerty [31] that participants whose attention distribution is more extensive could consider the information of each functional area in the simulated tower control interface and have a better SA. Regardless of the group, the participants' SA decreased as the experimental difficulty increased because increasing the experimental difficulty greatly increased the demand for attention resource (Demand), while the situational understanding Review 13 (1) (2020) 133 -140 (Understand) and the supply of attention resource (Supply) remained limited.…”
Section: Sa Of Tower Controllerssupporting
confidence: 92%
“…The independent sample t-test for the different groups' number of errors in the simple, medium, and difficult experiments showed a nearly significant difference between the dispersed and clustered groups (the respective p values of the simple, medium, and difficult experiments were 0.06, 0.05, and 0.01). Specifically, the participants whose fixation feature is dispersed distribution (NNI>1) had a better operation performance, which is inconsistent with the conclusion of Moore and Gugerty [31] that "Errors also increased as NNI increased towards 1, which indicates that the spatial distribution of fixations became less aggregated and more randomly dispersed". The possible reasons are as follows: (1) the interfaces of these two experiments were not the same, that is, Kristin's was based on the radar control interface, whereas ours was based on the simulated tower control interface.…”
Section: Performance Of Tower Controllerscontrasting
confidence: 73%
See 2 more Smart Citations
“…We used eye tracking to gain a deeper understanding of how participants build SA as a function of time. It is well known that eye movements are correlated with bottom-up and top-down attention (Borji and Itti, 2013;Henderson, 2003;Itti and Koch, 2001) and memory of visual objects (Irwin and Zelinsky, 2002;Moore and Gugerty, 2010). For example, using a SAGAT method, Moore and Gugerty (2010) found that the more participants fixated on an aircraft in an air traffic control task, the higher their SA (i.e., responses to state queries) for that aircraft.…”
Section: Introductionmentioning
confidence: 99%